Needs analysis of an integrated assessment instrument of chemical literacy and critical thinking among senior high school students and chemistry teachers - Dwi Ayuni, Amara; Yuliani, Galuh; Nahadi (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
Assessment had a significant influence on students’ learning processes. Assessment needed to continuously align with instruction and existing learning objectives. The goal of science education was to help students develop thinking skills to solve problems in everyday life. This study aimed to analyse the need for an integrated assessment of chemical literacy and critical thinking based on a literature review and empirical data. This study employed a qualitative descriptive method, grounded in a systematic literature review and an empirical field study involving chemistry teachers and high school students studying chemistry subject. The results indicated that the development of integrated assessment test could address the demands of 21st century education, teachers generally recognised the importance of chemical literacy and critical thinking in learning, but still had limitations in utilising appropriate assessment test, and many students still struggled to relate chemistry to everyday life, so their critical thinking skills to address chemical problems in real contexts were not practised through existing test items. These findings highlighted the need to develop an integrated assessment of chemical literacy and critical thinking that not only measured students’ understanding of chemistry concepts but also developed analytical skills to analyse and apply chemical knowledge in real-life situations.